The use of high–sensitivity sapphire cells in high pressure NMR spectroscopy and its application to proteins. Issue 2 (2004) - Kremer Kremer, W. W.; Arnold Arnold, M. R. M. R.; Kachel Kachel, N. N.; Kalbitzer Kalbitzer, H. R. H. R.
Abstract : The application of high pressure in bioscience and biotechnology has become an intriguing field in un/refolding and misfolding processes of proteins. NMR spectroscopy is the only generally applicable method to monitor pressure–induced structural changes at the atomic level in solution. Up to now the application of most of the multidimensional NMR experiments is impossible due to the restricted volume of the high pressure glass cells which causes a poor signal–to–noise ratio. Here we present high strength single crystal sapphire cells which double the signal–to–noise ratio. This increased signal–to–noise ratio is necessary to perform, for example, phophorus NMR spectroscopy under variable pressures. To understand the effect of pressure on proteins, we need to know the pressure dependence of 1 H chemical shifts in random coil model tetrapeptides. The results allow distinguishing structural changes from the pressure dependence of the chemical shifts. In addition, the influence of pressure on the buffer system was investigated. Since high pressure was shown to populate intermediate amyloidogenic states of proteins the investigation of pressure effects on proteins involved in protein conformational disorders like Alzheimer's Disease (AD) and Transmissible Spongiform Encephalopathies (TSE) is of keen interest. 1 H– 15 N–TROSY–spectra were acquired to study the effects of pressure and temperature on chemical shifts and signal volumes of the human prion protein. These measurements show identical pressure sensitivity of hu PrP(23–230) and hu PrP(121–230). First results suggest a folding intermediate for the human prion protein which can be populated by high hydrostatic pressure.